2019
DOI: 10.1186/s40164-019-0136-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel GTF2I–PDGFRB and IKZF1–TYW1 fusions in pediatric leukemia with normal karyotype

Abstract: Background Many cases of acute lymphoblastic leukemia (ALL) carry visible acquired chromosomal changes of pathogenetic, diagnostic, and prognostic importance. Nevertheless, from one-fourth to half of newly diagnosed ALL patients have no visible chromosomal changes detectable by G-banding analysis at diagnosis. The introduction of powerful molecular methodologies has shown that many karyotypically normal ALLs carry clinically important submicroscopic aberrations. Case presentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Three recurrent gene mutations (RUNX1, ASXL1, and TP53) have been added in the risk stratification of the ELN-2017 recommendations for AML [2]. Recently, more novel fusion genes, such as GTF2I-PDGFRB and IKZF1-TYW1 fusion genes, and PAN2/PAN3 complex, have reported and may be clinically important [120,121]. As the new technology advances, more recurrent gene mutations will be explored and used for AML risk stratification and treatment guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…Three recurrent gene mutations (RUNX1, ASXL1, and TP53) have been added in the risk stratification of the ELN-2017 recommendations for AML [2]. Recently, more novel fusion genes, such as GTF2I-PDGFRB and IKZF1-TYW1 fusion genes, and PAN2/PAN3 complex, have reported and may be clinically important [120,121]. As the new technology advances, more recurrent gene mutations will be explored and used for AML risk stratification and treatment guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…With increased recognition of cryptic PDGFRB rearrangements and the associated exquisite sensitivity to TKI therapy, 12,14–16 it has become necessary to screen cases for this abnormality with methods beyond conventional karyotyping. RNA sequencing is a sensitive method for detecting PDGFRB rearrangements; however, it is not readily available in most clinical laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…To date, >40 fusion partners of PDGFRB have been reported, with t(5;12)(q33;p13)/ ETV6 – PDGFRB being the most common 8–14 . The disease is usually suspected in the presence of a rearrangement involving chromosome 5q31–33 on conventional karyotyping, which can be confirmed with fluorescence in‐situ hybridisation (FISH) studies to assess involvement of PDGFRB .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, double homeobox A pseudogene 10, located in chr14q11.2, promotes an aggressive phenotype by binding lysine-specific histone demethylase 1 and repressing large tumor suppressor kinase 2 and Ras-related glycolysis inhibitor and calcium channel regulator expression levels in NSCLC (17). Furthermore, previous studies have revealed that chr14q11.2 may participate in cancer development (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%